A concept analysis of psychological safety: Further understanding for application to health care - Ayano Ito; Kana Sato; Yoshie Yumoto; Miki Sasaki; Yasuko Ogata (Wiley, 2022)
Abstract Aim To clarify the concept of psychological safety in a healthcare context and to provide the first theoretical framework for improving interpersonal relationships in the workplace to better patient care. Design A Rodgers' concept analysis. Methods The concept analysis was conducted using a systematic search strategy on PubMed, CINAHL, PsycINFO and Ichushi‐Web. Results An analysis of 88 articles studying psychological safety in health care identified five attributes: perceptions of the consequences of taking interpersonal risks, strong interpersonal relationships, group‐level phenomenon, safe work environment for taking interpersonal risks and non‐punitive culture. The antecedents included structure/system factors, interpersonal factors and individual factors. The four consequences included performance outcomes, organizational culture outcomes, and psychological and behavioural outcomes.